2012
DOI: 10.1177/1352458512444327
|View full text |Cite
|
Sign up to set email alerts
|

The quality of reports of randomized trials in multiple sclerosis: a review

Abstract: Randomized clinical trials (RCT) in multiple sclerosis (MS) have a recent tradition, but their number has been exponentially increasing since the first study detecting the efficacy of a disease modifying drug in MS. To examine the methodological details of reports of RCT in MS, we extracted from five leading journals all the reports of RCT published between 1993 and 2010. Trial reports were compared for different periods (1993-2001, 2002-2006, 2007-2010) for a set of indicator variables reflecting methodologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
1
6
0
1
Order By: Relevance
“…7 While growing numbers of eligibility criteria reflect the increasing understanding and complexity of possible influences on outcome variables such as the trial ARR, early trials with fewer eligibility criteria might have been more susceptible to such influences than modern ones. Similarly, changing definitions of MS and relapses, as well as varying forms of report, confirmation and treatment in the case of relapses undoubtedly play a role, as was suggested by Inusah et al 7 The OQS scores of the trials in RMS generally increased over time, reflecting higher trial quality or better reporting, as described in Signori et al 15 Since the relative incidence of MS in women compared to men has risen from 2:1 to 4:1 over recent years, 16 we were surprised to find stability in the proportion of patients who were women. Held et al show a correlation between on-study relapse rates and female sex, 17 and therefore changes in the gender ratio over time could potentially have explained part of the temporal trends in trial ARR.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…7 While growing numbers of eligibility criteria reflect the increasing understanding and complexity of possible influences on outcome variables such as the trial ARR, early trials with fewer eligibility criteria might have been more susceptible to such influences than modern ones. Similarly, changing definitions of MS and relapses, as well as varying forms of report, confirmation and treatment in the case of relapses undoubtedly play a role, as was suggested by Inusah et al 7 The OQS scores of the trials in RMS generally increased over time, reflecting higher trial quality or better reporting, as described in Signori et al 15 Since the relative incidence of MS in women compared to men has risen from 2:1 to 4:1 over recent years, 16 we were surprised to find stability in the proportion of patients who were women. Held et al show a correlation between on-study relapse rates and female sex, 17 and therefore changes in the gender ratio over time could potentially have explained part of the temporal trends in trial ARR.…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, changing definitions of MS and relapses, as well as varying forms of report, confirmation and treatment in case of relapses undoubtedly play a role, as has been suggested by Inusah et al [7]. The Oxford Quality Scale scores of the trials in RMS generally increased over time -reflecting higher trial quality or better reporting as described [15].…”
Section: Discussionmentioning
confidence: 91%
“…Finally, 32.5% showed baseline demographic and clinical characteristics, and 25% performed an intent-to-treat analysis. In a review 40 of 53 clinical trials on multiple sclerosis, the authors found that 79% were sponsored by a pharmaceutical company, 13% had mixed funding and only 6% were funded by non-profit institutions. This might compromise the validity of this trial, since funding is clearly biased, just the opposite of what we found in our review.…”
Section: Discussionmentioning
confidence: 99%
“…Por último, el 32.5% mostraron las características demográficas y clínicas basales, y el 25% realizaron un análisis por intención de tratar. En una revisión 40 de 53 ensayos clínicos sobre esclerosis múltiple, los autores encontraron que el 79% fueron patrocinados por una compañía farmacéutica, el 13% fue con financiamiento mixto y solo el 6% por instituciones sin ánimo de lucro. Esto podría comprometer la validez de este estudio, pues es un financiamiento claramente sesgado, justo lo opuesto a lo encontrado en nuestra revisión.…”
Section: Discussionunclassified